Fototransformator Asam Humat menggunakan Semikonduktor TiO2 Doping Cu - Rahma Zila; Rahadian Zainul (Departemen Kimia FMIPA UNP, 2019)
Synthesis of Cu doping TiO2 was carried out by sol-gel method, Cu concentration used was 5% calcined at 4000C then characterized by XRD then applied to degrade humic acid using a variation of hours ie 1 to 5 hours, optimum decrease in humic acid occurred at 3 hour which is 52.21%.